ANALISIS PENGARUH UPAH MINIMUM TERHADAP KESEMPATAN KERJA SEKTOR INDUSTRI DENGAN PANEL DATA ANALYSIS - Pusposari, Luthfiya Fathi (IQTISHODUNA, 2010)
This study aims to determine the effect of minimum wages and employment of industrial sector in East Java. Researchers include two control variables are GDP as control variable of demand labor and work force as control variable of supply labor by using panel data from all districts and cities in East Java (29 districts and nine cities). Analysis of this study used panel data analysis which consisting of the Common Effect model, Fixed Effect model and Random Effect model, then chosed the most appropriate model. The result of this study show after testing the models, the appropriate model is fixed effect where minimum wages have negative effect of employment in industrial sector in east java.